2020
DOI: 10.1080/10669817.2020.1719299
|View full text |Cite
|
Sign up to set email alerts
|

Trigger point dry needling, manual therapy and exercise versus manual therapy and exercise for the management of Achilles tendinopathy: a feasibility study

Abstract: Background:The effect of trigger point dry needling (TDN) on myofascial trigger points (MTP) in Achilles tendinopathy are unknown. Objectives: To determine the feasibility of a large randomized controlled trial (RCT) to compare the effects of TDN to exercise in a patient population with Achilles tendinopathy. Methods: This single-factor, pretest-posttest control group design included 22 subjects between the ages of 24 and 65 years with Achilles tendinopathy. Subjects were randomly assigned to either a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 150 publications
(506 reference statements)
0
2
0
Order By: Relevance
“…2) [28,29,45,71,76,100,109,150,152,153,160,190,201,203,216,217,231,232,238,241,269,270,292,302,311]. The single leg heel rise test was the most frequently reported specific test (13 studies) [48,63,89,90,107,108,200,212,216,242,259,310,311]. Other outcome measures included measures of ability to walk, jump and balance.…”
Section: Physical Function Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…2) [28,29,45,71,76,100,109,150,152,153,160,190,201,203,216,217,231,232,238,241,269,270,292,302,311]. The single leg heel rise test was the most frequently reported specific test (13 studies) [48,63,89,90,107,108,200,212,216,242,259,310,311]. Other outcome measures included measures of ability to walk, jump and balance.…”
Section: Physical Function Capacitymentioning
confidence: 99%
“…'Ankle range of motion' was reported in 4% (13/307) of the studies [17, 45, 48, 63-66, 85, 203, 242, 259, 296] and one study [259] reported first metatarsophalangeal joint range of motion. 'Pain and or tenderness with palpation' was reported in 4% (11/307) of the studies [18,37,45,48,53,77,98,113,207,234,279], and 'Sensory modality specific pain' was reported in 4% (14/307) of the studies [13,42,49,60,65,90,94,105,108,177,215,218,238,309].…”
Section: Achilles Tendinopathy Specific Domainsmentioning
confidence: 99%